2023
DOI: 10.3390/nano13061076
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Tetracycline with Photocatalysis by CeO2-Loaded Soybean Powder Carbon

Abstract: In the process of using photocatalysts to treat tetracycline (TC) wastewater, the degradation efficiency of soybean powder carbon material (SPC) can be improved by loading it with cerium oxide (CeO2). In this study, firstly, SPC was modified by phytic acid. Then, the CeO2 was deposited on modified SPC using the self-assembly method. Catalyzed cerium (III) nitrate hexahydrate (CeH3NO4) was treated with alkali and calcined at 600 °C under nitrogen. XRD, XPS, SEM, EDS, UV-VIS /DRS, FTIR, PL and N2 adsorption–deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…, carboxyl, phenol, hydroxyl, and acid anhydride) that promote contaminant removal. 20 However, BC cannot provide sufficient electrons for PMS activation, which results in lower catalytic efficiency. 21 Studies have shown that the introduction of metals can improve PMS activation.…”
Section: Introductionmentioning
confidence: 99%
“…, carboxyl, phenol, hydroxyl, and acid anhydride) that promote contaminant removal. 20 However, BC cannot provide sufficient electrons for PMS activation, which results in lower catalytic efficiency. 21 Studies have shown that the introduction of metals can improve PMS activation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, He et al studied CeO 2 loaded soybean powder carbon as a photocatalyst for TC degradation. 21 As a comparison, they tested CeO 2 obtained by the cerium( iii ) nitrate hexahydrate (CeH 3 NO 4 ) treated with alkali and calcined at 600 °C under nitrogen without soybean powder carbon. The result, after 180 min indicate only 20% of TC removal.…”
Section: Introductionmentioning
confidence: 99%